Antiviral activity of SP81 peptide against Enterovirus A71 (EV-A71) - Noraini, Abd-Aziz *; Lee, Michelle Felicia *; Ong, Seng Kai *; Poh, Chit Laa * (Elsevier, 2024)
The hand, food, and mouth disease (HFMD) is primarily caused by Enterovirus A71 (EV-A71). EV-A71 outbreaks in the Asia Pacific have been associated with severe neurological disease and high fatalities. Currently, there are no FDA-approved antivirals for the treatment of EV-A71 infections. In this study, the SP81 peptide, derived from the VP1 capsid protein of EV-A71 was shown to be a promising antiviral candidate for the treatment of EV-A71 infections. SP81 peptide was non-toxic to RD cells up to 45 μM, with a half-maximal cytotoxic concentration (CC50) of 90.32 μM. SP81 peptide exerted antiviral effects during the pre- and post-infection stages with 50% inhibitory concentrations (IC50) of 4.529 μM and 1.192 μM, respectively. Direct virus inactivation of EV-A71 by the SP81 peptide was also observed with an IC50 of 8.076 μM. Additionally, the SP81 peptide exhibited direct virus inactivation of EV-A71 at 95% upon the addition of the SP81 peptide within 5 min. This study showed that the SP81 peptide exhibited significant inhibition of EV-A71 and could serve as a promising antiviral agent for further clinical development against EV-A71 infections.